Rates of Minimally Invasive Surgery After Introduction of Robotic-Assisted Surgery for Common General Surgery Operations - Zhi Ven Fong, MD, MPH, DrPH; Elizabeth Wall-Wieler, PhD; Shaneeta Johnson, MD; Richard Culbertson, PhD; Brian Mitzman, MD, MS (Annals of Surgery Open)
Importance:. Many patients who would benefit from minimally invasive surgery (MIS) have open surgery; robotic-assisted surgery (RAS) addresses some of the limitations of laparoscopic surgery and could increase rates of MIS across different patient populations. Objective:. To determine whether the introduction of RAS increases MIS rates and whether increases are seen across different patient populations undergoing common general surgery procedures. Design:. A retrospective cohort study was performed to compare rates of MIS in the year before and after the index date for hospitals that did and did not introduce RAS. Generalized estimating equation regression models were used to compare rates in MIS over time. Setting:. PINC AI Healthcare Database, an all-payor discharge database of hospitals in the United States. Participants:. Hospitals that performed cholecystectomy, inguinal hernia repair, ventral hernia repair, and colorectal resection from 2016 to 2022. Exposure:. RAS hospitals performing at least 1 common general surgery procedure using RAS. Main Outcome and Measure:. The primary analysis examined rates of MIS, defined as the rate of common general surgeries that were minimally invasive (laparoscopic or RAS) in a hospital. The secondary analysis examined MIS rates for common general surgeries, across age, sex, race, ethnicity, and payor. Results:. Of 408 hospitals included in the study, 153 (38%) introduced RAS for common general surgeries. The relative MIS rate for hospitals that introduced RAS compared with hospitals that did not went from 1.08 (95% confidence interval [CI], 1.02–1.14; P < 0.01) before the index date to 1.15 (95% CI, 1.09–1.22; P < 0.01) after the index date (Pinteraction < 0.01), indicating a larger increase in MIS rates among hospitals introducing RAS. MIS rates increased significantly more in hospitals that introduced RAS across patient age, sex, ethnicity, race, and payor compared with hospitals that did not introduce RAS. Conclusions and Relevance:. Hospitals that introduced RAS for common general surgery procedures were associated with an increase in MIS rates across different patient populations compared with hospitals that did not introduce RAS.